Model for evaluating outsourcing logistics companies in the COVID-19 pandemic - Cheng-An Tsai; Tien-Hwa Ho; Jyh-Shyan Lin; Chien-Chih Tu; Che-Wei Chang (Logistics, 2021)
The COVID-19 pandemic has severely affected the world's manufacturing industry, particularly in terms of the continued increase in logistics costs that has led to an increase in business operating costs. This study proposes a two-stage model for evaluating the most appropriate outsourcing logistics companies for a manufacturing factory. In the first stage, a modified Delphi method was used to recruit experienced experts to determine criteria for evaluating outsourcing logistics vendors and establish a hierarchical structure. In the second stage, the analytic hierarchy process (AHP) was used to evaluate suitable logistics companies based on the hierarchical structure. Finally, a case study was conducted to demonstrate the suitability of the two-stage model for evaluating outsourcing logistics companies for reducing logistics costs while maintaining service quality. The proposed model can be used as a basis for evaluating outsourcing logistics companies.
Keywords: 650; analytic hierarchy process; COVID-19 pandemic; Delphi method; logistics; outsourcing